Was ist von Arthur Schnitzlers Briefwechsel mit Autoren und Autorinnen Neues zu erwarten? [What novelties are to be expected from Arthur Schnitzler’s correspondence with other writers?] (Studia austriaca, 2019)
A first insight into a new digital edition project of Arthur Schnitzler’s correspondence with eighty-six writers is the basis for a discussion of the methodological and epistemological transformations in editing in the last five decades. As a modernist writer, Schnitzler is one of the protagonists of the culture of letters. Bringing his correspondence into relation with his diary aims at not only reconstructing his “life” and “work”, but at visualizing transnational correspondence networks.